Again with Education for citizenship. Policy and pedagogy - Juan-Carlos HERNÁNDEZ BELTRÁN (Ediciones Universidad de Salamanca, 2013)
The Organic Law of Education was passed in may 2006. From then to now, the subject called Education for citizenship has been one of the on-going debate not only in education field but also in policy. As a result of its development, there has been an interesting discussion between people who are against and, on the other hand, people who are for. In this paper we try to show that education for citizenship is taught in most of European countries.